The determinant of capital expenditure: empirical evidence from Bursa Malaysia / Mohd Ariff Ridzuan Mohd Asih - Mohd Asih, Mohd Ariff Ridzuan (2019)
The aim of this study was to determine the effect of free cash flow, dividend payout ratio and investment opportunities on capital expenditure of companies listed at the Bursa Malaysia. Companies engage in various ways to finance their investments, including equity financing (internally generated funds and externally raised funds) and or debt. Free cash flow tempts managers to expand the scope of operations and the size of the firm, these spending is seen as unprofitable especially to the shareholders, who see it worthwhile for the firm to issue dividends instead of retaining the funds to invest. The study aimed at determining the the effect of the level of free cash flow and the amount of extra cash that can be committed on investment decisions by companies that are listed at the Bursa Malaysia. Data was obtained from annual statements of listed companies. The study covered a five year period from 2013 to 2017. Multiple linear regression method was used to identify the existence of the relationship. The regression model results point out that Free cash flow have a positive impact on Net Capital Expenditure. From the organizations considered, it was established that there is a positive fairly insignificant relationship between dividend payout ratio and capital expenditure. This study used only three variables as the measures of the relationship between free cash flows, dividend payout ratio and investment opportunities on investments, hence there is need to carry out the study with other different factors in order to be able to establish whether there are other major factors that have a relationship with capital expenditure at the Bursa Malaysia and in companies not listed at the Bursa Malaysia.